Empirical representation of firms' employment decisions by an (S,s) rule - Paola Rota (Fondazione Eni Enrico Mattei (FEEM), 2001)
We analyse the conditions under which an (S,s) rule may be derived and compare these with alternative rules. We consider the case of labour demand with fixed adjustment costs. The (S,s) rule implies a specific ordering of choices: downward adjustment, non-adjustment and upward adjustment with the decision of inaction lying crucially in the middle. We may model firms' decisions as an (S,s) rule only if it is possible to characterise unobserved heterogeneity as an exact negative relation between the choice-specific error terms. Assuming that these are normally distributed, the particular ordering of choices implied by the (S,s) rule may be estimated by an ordered probit. We test the (S,s) rule nesting the ordered probit within a multinomial model with correlated error terms. We find that restriction of univariate error distribution is rejected by the data.
Keywords: C25; J23; 330; (S; s) rules; adjustment costs; probit models; Arbeitsnachfrage; Anpassungskosten; Entscheidung; Theorie